2003
DOI: 10.1124/jpet.103.054965
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Cell Gene Profiling of Ventral Tegmental Dopamine Neurons after Acute and Chronic Cocaine Self-Administration

Abstract: Chronic cocaine administration induces a number of biochemical alterations within the mesolimbic dopamine system that may mediate various aspects of the addictive process such as sensitization, craving, withdrawal, and relapse. In the present study, rats were allowed to self-administer cocaine (0.5 mg/ infusion) for 1 or 20 days. Tyrosine hydroxylase immunopositive cells were microdissected from the ventral tegmental area (VTA) using laser capture microdissection, and changes in the abundances of 95 mRNAs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 61 publications
3
47
0
Order By: Relevance
“…7,8,19 In addition to the cocaine-induced NAc plasticity, studies in rodent models indicate persistent or even permanent biochemical alterations in regions associated with the mesolimbic dopamine pathway including upregulation of the cyclic AMP (cAMP) pathway, [20][21][22][23][24][25][26] activator protein 1 family members [27][28][29][30][31][32] as well as glutamate, dopamine, gaminobutyric acid (GABA) and opiate receptors, growth factors, cytoskeletal elements and cell metabolism. [33][34][35][36][37][38][39][40][41] Genomic analyses in human post-mortem tissue of cocaine overdose (COD) victims have confirmed the findings of studies employing rodent models and have revealed novel mechanisms of drug-induced neuronal and non-neuronal dysregulation in human post-mortem brain tissue. [42][43][44][45] For example, Bannon and co-workers 42 examined gene expression in the NAc of post-mortem brain tissue of human cocaine abusers and controls and found significant alterations in several novel functional classes and transcripts including signal transduction, transcriptional and translational processing, neurotransmission and synaptic function, glia, structural and cell adhesion, receptors/transporters/ion channels, cell cycle and growth and lipid and protein processing.…”
Section: Introductionmentioning
confidence: 79%
“…7,8,19 In addition to the cocaine-induced NAc plasticity, studies in rodent models indicate persistent or even permanent biochemical alterations in regions associated with the mesolimbic dopamine pathway including upregulation of the cyclic AMP (cAMP) pathway, [20][21][22][23][24][25][26] activator protein 1 family members [27][28][29][30][31][32] as well as glutamate, dopamine, gaminobutyric acid (GABA) and opiate receptors, growth factors, cytoskeletal elements and cell metabolism. [33][34][35][36][37][38][39][40][41] Genomic analyses in human post-mortem tissue of cocaine overdose (COD) victims have confirmed the findings of studies employing rodent models and have revealed novel mechanisms of drug-induced neuronal and non-neuronal dysregulation in human post-mortem brain tissue. [42][43][44][45] For example, Bannon and co-workers 42 examined gene expression in the NAc of post-mortem brain tissue of human cocaine abusers and controls and found significant alterations in several novel functional classes and transcripts including signal transduction, transcriptional and translational processing, neurotransmission and synaptic function, glia, structural and cell adhesion, receptors/transporters/ion channels, cell cycle and growth and lipid and protein processing.…”
Section: Introductionmentioning
confidence: 79%
“…Dysfunction or degeneration of these neurons leads to pathologies such as Parkinson's disease and addiction. A number of microdissection studies investigating molecular events in dopamine neurons have been carried out (Backes and Hemby 2003;Grimm et al 2004;Chung et al 2005;Greene et al 2005;Yao et al 2005;Cantuti-Castelvetri et al 2007;Stephenson et al 2007;Gründemann et al 2008;Lammel et al 2008). However, not all have immunolabeled to identify dopamine neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, repeated cocaine administration has been shown to cause upregulation of CaMKII expression in the VTA (Backes and Hemby, 2003;Licata et al, 2004). Therefore, differential regulation of the CaMKII-dependent desensitization mechanism may contribute to the difference in D 2 autoreceptor sensitivity, that is, increase vs decrease, following repeated intermittent administration of alcohol vs psychostimulants.…”
Section: Enhanced D 2 Autoinhibition and Hypodopaminergic State Durinmentioning
confidence: 99%